2021
DOI: 10.1108/bij-03-2021-0132
|View full text |Cite
|
Sign up to set email alerts
|

Modelling enablers of efficiency and sustainability of healthcare: a m-TISM approach

Abstract: PurposeIt would not be an exaggeration to say that healthcare is the most crucial one in today's perspective. The healthcare sector, in general, is engaged in working on various dimensions simultaneously like the safety, care, quality and cost of services, etc. Still, the desired outcomes from this sector are far away, and it becomes pertinent to address all such issues associated with healthcare on a priority basis for sustaining the outcomes in a long-term perspective. The present study aims to explore the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…Future researchers are also encouraged to use m-TISM as a simpler and more convenient way of constructing structural explanatory models to validate their results and findings if there are fewer variables, the field of study is well established and the relevant literature is extensive. [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Future researchers are also encouraged to use m-TISM as a simpler and more convenient way of constructing structural explanatory models to validate their results and findings if there are fewer variables, the field of study is well established and the relevant literature is extensive. [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Suppose if there are ten values, then the total number of paired comparisons done in the research work is 45 in TISM. Whereas in m-TISM, only 15 comparisons are required for getting the result that reveals that in m-TISM, the paired comparison is reduced by one-third time (Sindhwani et al. , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Suppose if there are ten values, then the total number of paired comparisons done in the research work is 45 in TISM. Whereas in m-TISM, only 15 comparisons are required for getting the result that reveals that in m-TISM, the paired comparison is reduced by one-third time (Sindhwani et al, 2021). Next, the transitivity is checked for every enabler; if A is transitive to B and B is transitive to C, then A is transitive to C according to the transitivity rule.…”
Section: Exploring Resilience In Msme Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…By application of approach such as analytic hierarchy process (AHP) the interdependencies between the factors cannot be observed (Mittal et al , 2019). Singh et al (2019) observed that DEMATEL is the preferred technique over AHP, total interpretive structural modeling, interpretive structural modeling or any multiple-criteria decision making techniques as it dissevers challenges into cause and effect group and indicates the severity of their effects too (Sindhwani et al , 2018; Shanker et al , 2019; Sindhwani et al , 2019a; Sindhwani et al , 2021). Bai and Satir (2020) stated that DEMATEL has a range to respond (0, 1, 2, 3 and 4) to explore the relationship between factors and further help in formulating futuristic strategies.…”
Section: Methodsmentioning
confidence: 99%